Beta-Lapachone Attenuates BMSC-Mediated Neuroblastoma Malignant Transformation by Inhibiting Gal-3/Gal-3BP/IL6 Axis - Zhou, Yang; Yan, Hui; Zhou, Qiang; Feng, Ruiling; Wang, Penggao; Yang, Fang; Zhang, Yaodong; Yuan, Ziqiao; Zhai, Bo (Frontiers in Pharmacology, 2021)
The inflammatory factor IL6 secreted by bone marrow mesenchymal stem cells (BMSCs) in the tumor microenvironment (TME) facilitates the survival and therapeutic resistance of neuroblastoma (NB). Here, we found that IL6 expression in primary tumor tissues or bone marrow (BM) metastases was closely associated with the disease risk and prognosis of NB patients. IL6 secretion from immortalized BMSC (iBMSC) was directly regulated by NB cells and is involved in promoting the proliferation and metastasis of NB cells. Beta-Lapachone (ARQ-501, LPC), an ortho-naphthoquinone natural product, significantly prevented the iBMSC-induced malignant transformation effect on NB cells through suppressing the expression and secretion of IL6 from iBMSC in vitro and in vivo. Mechanistically, LPC disrupted the crosstalk between NB cells and iBMSC in an NQO1-dependent manner through blocking the Gal-3BP/Gal-3/IL6 axis. Our results reveal the effect of iBMSC-derived IL6 on TME-induced malignant transformation of NB cells, and provide theoretical basis for the clinical application of LPC as a potential IL6 inhibitor in high-risk refractory NB patients.